Pollen morphology of the least known families of the order Asterales - Tellería, María Cristina; Barreda, Viviana Dora; Palazzesi, Luis (Review of Palaeobotany and Palynology)
The recent discovery of pollen grains assigned to the earliest branch of Asteraceae from Cretaceous sediments in Antarctica prompted us to examine the pollen from five lesser known members of Asterales (Alseuosmiaceae, Argophyllaceae, Pentaphragmataceae, Phellinaceae and Roussaceae) that might also be represented in fossil sediments. Detailed pollen morphology in the basal members of the order Asterales has, until now, been incomplete. Our study reveals a highly variable pollen morphology of these small, and poorly explored families. The tricolporate character of Phelline macrophylla and the zono-hexaporate aperture of Roussea simplex are described for the first time. Pollen of Alseuosmiaceae share granulate structure and tectum little sculpturate, with the exception of Periomphale which is verrucate; Crispiloba has an isolated position due to very large size and porate aperture. Pollen of Argophyllaceae is relatively homogeneous sharing tricolporate aperture, tectum little sculpturate and columellate structure. Pentaphragmataceae is distinguished by its smallest pollen, with oblate-peroblate shape, di or tricolporate aperture and psilate exine. Roussaceae is the most diverse family at level of dispersion unit, aperture type, sculpture and structure of exine. The morphological characters here analysed can be potentially used to unmask fossil dispersed pollen grains with unknown botanical affinity. Fil: Tellería, María Cristina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Laboratorio de Sistemática y Biología Evolutiva; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - La Plata; Argentina Fil: Barreda, Viviana Dora. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina Fil: Palazzesi, Luis. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación ...